Marxism development: methodological possibilities of synergetics - Mikhailouski, Vadzim S. (Journal of the Belarusian State University. Sociology, 2019)
Objective of the article is to reveal methodological synergy opportunities for the development of Marxism. Methodological basis of the research contained general scientific methods (historic, comparative, system method) and a private method of social science (content-analysis). Phased formation of the Marxism was analyzed. Particular methodological synthesis of Marxism and Freudianism, existentialism, phenomenology, structuralism and semiotics were revealed. Methodological difficulties of modern Marxism in describing the global order and the methodological possibilities of synergy to overcome them were determined. New methodology of social cognition – synergistic Marxism – was proposed. Object, subject, aim and tasks of synergistic Marxism were indicated. Materials of the article may be used in educational process and scientific research.